Effect Of Price, Service Quality And Promotion On Customer Satisfaction (GRAB): Effect Of Price, Service Quality And Promotion On Customer Satisfaction (GRAB) - Vallery Vallery; Happy Novita; Sufika Sary (Jurnal Mantik, 2020)
The purpose of this study was to examine and analyze the effect of price, service quality and promotion on satisfaction of using online transportation services (Grab) Medan. Grab user satisfaction has decreased due to high tariff prices, unsatisfactory services and less effective promotion of Grab. The population and sample in this study amounted to 100 Grab customers in Medan City. The research method uses multiple linear techniques. Hypothesis testing used in this research is partial test and simultaneous test. The magnitude of the coefficient of determination is 72.6% and the remaining 27.4% customer satisfaction is explained by other causes such as consumer motivation and trust. The conclusions in this study indicate that simultaneously price, service quality and promotion have positive and significant effect on satisfaction of using online transportation services (Grab) Medan and partially price, service quality and promotion have positive and significant effect on satisfaction of using online transportation services (Grab) Medan.